Four treasures of the sky [large type] - Zhang, Jenny (Thorndike Press large print core, 2022)
"Daiyu never wanted to be like the tragic heroine for whom she was named, revered for her beauty and cursed with heartbreak. But when she is kidnapped and smuggled across an ocean from China to America, Daiyu must relinquish the home and future she imagined for herself. Over the years that follow, she is forced to keep reinventing herself to survive. From a calligraphy school, to a San Francisco brothel, to a shop tucked into the Idaho mountains, we follow Daiyu on a desperate quest to outrun the tragedy that chases her. As anti-Chinese sentiment sweeps across the country in a wave of unimaginable violence, Daiyu must draw on each of the selves she has been-including the ones she most wants to leave behind-in order to finally claim her own name and story. At once a literary tour de force and a groundbreaking work of historical fiction, Four Treasures of the Sky announces Jenny Tinghui Zhang as an indelible new voice. Steeped in untold history and Chinese folklore, this novel is a spellbinding feat"--